A novel frameshift variant of PAX3 in a Chinese Yugur family with Waardenburg syndrome type 1 - Zhan, Lupeng; Xu, Baicheng; Lin, Dujuan; Wang, Ya; Bian, Panpan (Frontiers in Genetics, 2025)
IntroductionWaardenburg syndrome type 1 (WS1) is a rare autosomal dominant disorder characterized by congenital sensorineural hearing loss and facial dysmorphisms. PAX3 mutations are a known genetic cause. This study investigated a novel PAX3 mutation in a Chinese Yugur family and assessed long-term auditory outcomes after cochlear implantation.Methods and ResultsWhole-exome and Sanger sequencing were used to identify causative variants, followed by bioinformatic analyses to predict pathogenicity. Auditory and speech rehabilitation were evaluated over a 7-year follow-up. A novel heterozygous frameshift mutation in PAX3 (c.788dup, p.Gln264ThrfsTer5) was identified and confirmed to be de novo. Structural modeling indicated disruption of a conserved domain, supporting its pathogenic role. The proband achieved excellent auditory and speech recovery and successfully integrated into mainstream education.DiscussionThis study expands the mutation spectrum of PAX3 and provides evidence supporting the pathogenicity of the c.788dup variant. It also confirms the long-term benefit of cochlear implantation and rehabilitation in WS1-related hearing loss.